"English Is Out There—You Have to Get with the Program": Linguistic Instrumentalism, Global Citizenship Education, and English‐Language Voluntourism. (11th December 2019) - Jakubiak, Cori
Abstract : English‐language voluntourism is a practice in which Global North, often young and inexperienced, volunteers teach English in the Global South on a short‐term basis as a form of alternative travel. Like other forms of volunteer tourism, English‐language voluntourism is characterized as global citizenship education for visiting volunteers and as development assistance for host communities. Drawing upon data collected as a part of a larger, multisited ethnography—which included participant‐observation in three different contexts, qualitative interviews with current and former volunteers, and a content analysis of English‐language voluntourism promotional materials—I argue that the practice's dominant discourses promote a limited view of language ‐in ‐education and development and the role(s) of civic action in social change. By framing short‐term, unskilled, English language teaching (ELT) as a Global South development initiative, English‐language voluntourism discourse extends to vulnerable others the same, individualistic, market‐based logic to which volunteers, themselves, are increasingly exposed. This logic defines nation‐states as economic competitors rather than guarantors of rights, and it casts the ideal citizen‐subject as a shape‐shifting, risk‐taking, life‐long learner who can mitigate economic volatility alone. For the most part, volunteer participants take up these discourses and frame their service as meeting one of two goals: increasing a nation‐state's competitive advantage by building its English language capacity, or helping individual people escape poverty alone by equipping them with the value‐added skill, English. Global citizenship education through English‐language voluntourism thus aligns with the interests of neoliberal governance rather than other, more progressive, social agendas, and it does little to help volunteers engage with the cultural politics of global ELT.